ROLE OF NEW PEDAGOGICAL TECHNOLOGIES IN IMPROVING PEDAGOGICAL PRACTICE - Tilabjonova Sevinch Shukhratovna (Western European Studies, 2024)
This article provides information about the role of new pedagogical technologies in the improvement of pedagogical practice and the effectiveness of improving the quality of education by using them in the classroom, as well as the conveniences and opportunities created by these technologies.
Keywords: teaching practice; new technologies; lesson